Pengaruh Pengetahuan, Modernisasi Strategi Direktoral Jenderal Pajak, Sanksi Perpajakan dan Religiusitas Yang Dipersepsikan Terhadap Kepatuhan Perpajakan - Rahmawaty, Stella; Baridwan, Zaki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The study’s purpose to examine the factors that influence an individual tax compliance who owns micro,small and medium enterprises in malang. The factors examined in this study is Knowledge, Strategy of Indonesia Taxation Authority, Tax Penalties and Religiosity. Ninety-five individuals possessing micro, small and medium enterprises located in malang are sampled. The sampling method that used was convenience sampling. The results of this study indicated that knowledge influence the attitude of tax compliance in performing tax compliance. Modernization strategy of Indonesia Taxation Authority, tax penalties and religiosity does not have an influence on tax compliance.Keywords : Knowledge, Strategy of Indonesia Taxation Authority, Tax Penalties, Religiosit, taxcompliance, UMKM